Chandra Anuloma Viloma Pranayama modifies Cardiorespiratory Functions - Prakash, S; Upadhyay-Dhungel, K (Janaki Medical College Journal of Medical Science, 2016)
Background and Objectives: In recent years, there has been considerable interest in scientific research on yoga, especially on Pranayama. Nostril breathing exercises including Alternate nostril breathing, Left nostril breathing and right nostril breathing exercises is getting attention in the east and in the west. Left nostril breathing exercises is also called Chandra Nadisuddhi Pranayama or Chandra anulomaa vilomaa Pranayama (CAV). Very few have carried out research on Chandra Anuloma Viloma Pranayama (CAV). This study was carried out to see the effects of CAV on experienced yoga practitioners and naïves.Material and Methods: The study consisted of 36 subjects divided into two groups, first group consist of 26 medical students who were naïve and the next group consist of 10 yoga practitioners. All the subjects performed 12 rounds of Chandra Nadisuddhi Pranayama in each session for 24 days. Variables were entered into SPSS Program and were analyzed.Results: This study depicts fall in Pulse rate, respiratory rate, systolic blood pressure and Diastolic blood pressure after CAV Pranayama in both Naïves and Yoga practitioners. But the significant drop was observed in SBP only (at p < 0.05) among Naives and in all parameters except respiratory rate among Yoga Practitioners.Conclusion: The effect of the Chandra Anuloma Viloma (CAV) in this study was more eminent in the yoga practitioners than in the naïve group.Janaki Medical College Journal of Medical Sciences (2015) Vol. 3 (1):45-51